Interactions between cassava varieties and soil characteristics in crop production in eastern Cameroon - Sarr, S.; Araki, S.; Njukwe, E. (Kyoto University, 2013)
Cassava represents a staple food source in Cameroon and in many other tropical countries, as it is effectively able to combat hunger. This study was carried out to: (i) determine the growth characteristics of improved and local cassava varieties in Eastern Cameroon under repeated cultivation, (ii) assess the effects of different soils on cassava growth, and (iii) disseminate the improved varieties throughout the region. The experiment was carried out during the 2010–2011 and 2011–2012 seasons. Two improved varieties, TMS-92/0326 and TMS-96/1414, and the local Ntolo variety were cultivated at three sites in a randomized block design with six replications. No fertilizer was applied and the fields were weeded regularly. A twoway ANOVA (variety x site) for each season showed that variety and site were equally significant, and there were no significant interactions between varieties and sites. The improved varieties had higher yields (2.0–5.5-fold higher) than Ntolo, with cassava mosaic disease having seriously affected the Ntolo yield. Soil acidity and organic matter content in the soil surface horizon may be major factors affecting the cassava yield, with TMS-92/0326 and Ntolo being tolerant of higher acidity than TMS-96/1414, which suggests that variety-soil interactions should be considered when improved varieties are introduced.